2005
DOI: 10.1111/j.0001-6349.2005.0255a.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum posterior uterine wall rupture in lower segment cesarean section scarred uterus

Abstract: examination showed two cystic tumors behind the uterus. Scand 84 2005

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Three cases of posterior uterine rupture in spontaneous labour are also recorded [10, 12, 13]. In our patient's case the fetal head was occipitotransverse prior to rupture.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Three cases of posterior uterine rupture in spontaneous labour are also recorded [10, 12, 13]. In our patient's case the fetal head was occipitotransverse prior to rupture.…”
Section: Discussionmentioning
confidence: 76%
“…In our patient's case the fetal head was occipitotransverse prior to rupture. Fetal malposition with an occipitoposterior position has previously contributed to posterior uterine ruptures, as has malpresentation with a transverse lie and dead fetus [12, 13]. Malposition alters the distribution of contractile force and increases labour dystocia; certain malpresentations cause uterine hyperdistension, which may also precipitate atypical uterine rupture.…”
Section: Discussionmentioning
confidence: 99%
“…[2,4] Whereas, isolated posterior uterine rupture is a very rare condition in unscarred uterus and have even been documented only a number of times in scared uterus. [4,[6][7][8][9][10][11][12][13][14] The cause of posterior uterine rupture in a scarred uterus remains not fully understood. Literature review suggests that other than the previous CS, an additional factor usually seems to play a role in causing the atypical site rupture.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the additional factors seem to be clear and could correlate with direct injury to the site of rupture, such as ectopic angular implantation, abnormal transverse fetal lie, or abnormal placentation. [5][6][7] However, in some cases the additional factors remain unclear. [8][9][10] In trial to explain the atypical site rupture in a scarred uterus, it has been suggested that the use of PG and/or oxytocin for induction could be the main factor.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In cases of posterior UR in patients of VBAC published between 1997 and 2007. [10][11][12][13][14] It is possible that uterine over distension predisposes weak thinned out musculature to atypical UR. Hawe and Olah and Figueroa et al reported two cases of posterior UR with the use of prostaglandin for induction of labor.…”
Section: Discussionmentioning
confidence: 99%